2015
DOI: 10.1111/pin.12369
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory myofibroblastic tumor‐like stromal proliferation within gastric inverted hyperplastic polyp

Abstract: Inflammatory myofibroblastic tumor-like stromal proliferation within gastric inverted hyperplastic polypTo the Editor: Gastric inverted hyperplastic polyp (IHP), a rare type of gastric polyp, is a downward-growing lesion composed of the proliferative gastric mucosal components of foveolar-, pyloric-, fundic-, or mixed-type epithelium that protrudes into the submucosal layer, mimicking a submucosal tumor. The pathogenesis of gastric IHP remains to be elucidated, although several hypotheses have been suggested. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 9 publications
1
12
1
Order By: Relevance
“…An EUS has been routinely performed for the qualitative diagnosis of SMT or to determine the depth of invasion of gastric tumors and has often revealed the presence of a multilocular anechoic region in the second or third layer of the gastric wall of the GHIP. 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 However, no specific features of GHIPs have been identified, and in the present series, the EUS revealed an atypical image of a cyst with partition walls and a hyperechoic nodule. In addition, previous reports showed that an EUS was performed in 25 patients (including six patients with adenocarcinoma components); however, no significant differences were noted in the EUS features of a GHIP with or without adenocarcinoma.…”
Section: Discussioncontrasting
confidence: 45%
See 3 more Smart Citations
“…An EUS has been routinely performed for the qualitative diagnosis of SMT or to determine the depth of invasion of gastric tumors and has often revealed the presence of a multilocular anechoic region in the second or third layer of the gastric wall of the GHIP. 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 However, no specific features of GHIPs have been identified, and in the present series, the EUS revealed an atypical image of a cyst with partition walls and a hyperechoic nodule. In addition, previous reports showed that an EUS was performed in 25 patients (including six patients with adenocarcinoma components); however, no significant differences were noted in the EUS features of a GHIP with or without adenocarcinoma.…”
Section: Discussioncontrasting
confidence: 45%
“…An EUS has been routinely performed for the qualitative diagnosis of SMT or to determine the depth of invasion of gastric tumors and has often revealed the presence of a multilocular anechoic region in the second or third layer of the gastric wall of the GHIP 7–27 . However, no specific features of GHIPs have been identified, and in the present series, the EUS revealed an atypical image of a cyst with partition walls and a hyperechoic nodule.…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…There is no radiological sign that serves as a diagnostic basis for gastric IMT [40][41][42][43][44][45]. Gastric IMTs have been reported to present as heterogeneous, lobar, calcified, cystic lesions on ultrasound and non-enhanced abdominal CT examinations [1], though they may manifest as homogeneous or heterogeneous lesions with central delayed enhancement and peripheral early filling [45,46].…”
Section: Radiological Diagnosismentioning
confidence: 99%